Arabinoxylans and the remaining protein fraction relationship with the gelling capability of the polysaccharide - Méndez-Encinas, Mayra Alejandra; Carvajal-Millan, Elizabeth; Rascón-Chu, Agustín; López-Franco, Yolanda Leticia; Lizardi-Mendoza, Jaime (Acta Universitaria, 2019)
Arabinoxylans (AX) are non-starch polysaccharides present in several tissues of cereal grains. These polysaccharides can form covalent gels through oxidative coupling of ferulic acid by the action of free radical-generating agents. Since the gelling capability of AX depends on their structural characteristics, the knowledge of structural characteristics and their effect on gel properties is essential for building a thorough understanding about the nature of these gels. Protein content of AX is one of such structural characteristics, whose impact on the gelling of the polysaccharide and gel properties has not been investigated in detail. Till date, it is not known how the protein is attached to the AX. This review presents research done on the arabinoxylan-protein association and the relationship of the protein fraction with the gelling capability of the polysaccharide, as well as the possible covalent binding on that association.